PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN PELANGGAN, DAN CORPORATE IMAGE TERHADAP KEPUASAN PELANGGAN INDONESIA TECHNOLOGY TREND - Christian, Michael; Setiobudi, Auditia (Universitas Ciputra Surabaya, 2023)
Abstract: Indonesia Technology Trend is a distribution business of technology and other trendy products. Theory of Cognitive Psychology is a theory which states that human behavior can’t be measured and explained without involving other mental processes. This research was conducted to determine the effect of (1) service quality on customer satisfaction (2) customer trust on customer satisfaction (3) corporate image on customer satisfaction of Indonesia Technology Trend. The method used for this research is descriptive quantitative by distributing surveys to 75 respondents who were determined using purposive sampling technique to random Indonesia Technology Trend consumers. The analysis tool of this research is SPSS. The result showed that service quality has no effect on customer satisfaction, customer trust has a significant positive effect on customer satisfaction, and corporate image has a significant positive effect on customer satisfaction.